Developing human movement system booklet as a biology teaching material suplement for XI grade students - S. Syamsurizal; Eka Aghnia Syarif; Rahmawati Rahmawati; Siska Alicia Farma (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Learning is a process of interaction between students and educators as considerable as learning resources in learning environment. The use of media in learning plays an important role in providing clearer explanation for difficult materials or concepts for students. This research aimed at developing booklet as a biology teaching suplement, especially in human movement system material for XI grade. This R&D research used the Plomp model which consisted of preliminary research, prototype development phase, and assessment phase. The data were analyzed qualitatively and quantitatively. The booklet developed was validated by 3 validators. The human movement system booklet for XI grade was categorized as very valid (94.11), stated as very practical by students (94.59) and teachers (92.19). It is suggested for teacher to use the human movement system booklet developed for XI graders.